Laparoscopic treatment of a solitary fibrous tumor originating in the cystic plate - Yu Kumagai (Surgical Case Reports, 2018)
Abstract Background Solitary fibrous tumor (SFT) is a rare mesenchymal tumor originating from the tissue underlying the mesothelial layer of the pleura or mediastinum. Other reported sites include the upper respiratory tract, orbit, thyroid, peritoneum, and central nervous system. Case presentation We describe a case of a 7 cm SFT that originated in the cystic plate. A liver tumor was an incidental finding in a 49-year-old woman during a regular radiological checkup for uterine fibroids. Imaging revealed a well-circumscribed solid mass between the gallbladder and liver. Intraoperative laparoscopy identified a soft tumor that had progressively expanded behind the gallbladder which was easily separated from the Laennec’s capsule of the liver. Hematoxylin and Eosin and immunohistochemical staining of the tumor tissue found both tangled and patterned arrangements of spindle cells consistent with a SFT derived from the subserosal layer of the gallbladder. Conclusions To the best of our knowledge, this is the first report of a SFT originating in the cystic plate.